FAKTOR PENENTU LOYALITAS PASIEN DI ERA REVOLUSI INDUSTRI 4.0 - Chrisandita, Putu Astrid Primastuti (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
ABSTRACTThis research aims to determine patient loyalty in the industrial revolution 4.0 in RSUP Sanglah Denpasar using quantitave research. The technique of data collection was conducted by giving quistionnaire to 200 respondents as samples. Data is analized on SEM and PLS (component based SEM). Result showed that: (1) the quality of service directly has positive and significant effect on the image of the hospital; (2) service quality directly has positive but not significant effect on patient loyalty; (3) the quality of service directly has positive and significant effect on patient satisfaction; (4) waiting time directly has positive and significant effect on hospital image; (5) waiting time directly has positive and significant effect on patient loyalty; (6) waiting time directly has positive and significant effect on patient satisfaction; (7) the image of the hospital directly has positive but not significant effect on patient satisfaction; (8) the image of the hospital directly has positive and significant effect on patient loyalty; (9) patient satisfaction directly has positive and significant effect on patient loyalty.Key words: patient loyalty; brand image; patient satisfaction;waiting time; service quality